Effects of subgrid scale and combustion modelling on flame structure of a turbulent premixed flame within LES and tabulated chemistry framework. Issue 5 (3rd September 2017) - Hosseinzadeh, Arash; Sadiki, Amsini; di Mare, Francesca; Janicka, Johannes
Abstract : The effects of combustion and SubGrid Scale (SGS) modelling on the overall flame characteristics of a turbulent premixed flame are investigated. This is achieved in terms of mean flow statistics, variances and flame surfaces. In particular, the chemical flame structure is analysed and compared. The Artificially Thickened Flame (ATF) approach coupled with the Flamelet Generated Manifolds (FGMs) and Filtered TAbulated Chemistry for LES (F-TACLES) approaches are used for this investigation. A Germano like procedure for dynamical calculation of SGS wrinkling is used which ensures the conservation of the total flame surface for both models. It turns out that using the dynamic SGS wrinkling model improves the results. Although the results of both combustion models in terms of statistics, mean and variances show very good agreement, the resolved flame surfaces hide different dynamic behaviour.